N-Heterocyclic carbene ligands bearing a naphthoquinone appendage: Synthesis and coordination chemistry. (8th January 2016) - Miłopolska, Ewa Adela; Kuss-Petermann, Martin; Neuburger, Markus; Wenger, Oliver; Ward, Thomas R.
Graphical abstract: Herein we report on the straighforward synthesis and coordination chemistry of an unsaturated N -heterocyclic carbene ligand bearing a naphthoquinone appendage. The electrochemical behaviour of the coinage metal complexes was scrutinized by cyclic voltammetry, revealing the potential of the NHC1 moiety to act as a redox active ligand. Abstract: Many biochemical transformations for small molecule functionalisation depend on the temporal delivery of multiple protons and electrons. For this purpose, Nature elegantly combines transition metals with redox-active cofactors. In a biomimetic spirit, we report on the synthesis and coordination chemistry of an N -heterocyclic carbene ligand bearing a naphthoquinone moiety NHC1 . Both the silver and palladium complexes [Ag(μ-Cl)(NHC1 )]2 2 and [Pd(η 3 -allyl)(NHC1 )Cl]5 were characterized by X-ray crystallography. Cyclic voltammetry of the metal complexes suggest that redox events occur both on the naphthoquinone and on the metal for the iridium and ruthenium complexes.